- The Role of Management by Objectives (MBO) in enhancing the impact of self-learning in the development of employees’ technical and interpersonal skills in startup companies – Case of Startup Companies in Lebanon - Shagri, Radwan Nazif (Journal of Economic, Administrative and Legal Sciences, 2018)
The adoption and the applying of the Management by Objectives (MBO) in the startups companies in Lebanon, is one of the most important roles that the owners, directors and head of departments must consider and implement it, thus this will contribute to reduce the lack of financial, human and other resources effectiveness. The startups companies in Lebanon generally depend on unprofessional work, although they are very enthusiastic and motivated. Moreover, management by Objectives (MBO) and measuring achievements are not secondary choices that can be ignored but they should be strengthened, encouraged and converted into a corporate culture in all operations within companies. Most of the startups companies, especially the Lebanese failed in the market from the first year, not because of economic conditions or weak financial resources, but because of the poor management, the preservation of existing resources and the unorganized work. Therefore, the objective of this study was to highlight the importance of Management by Objectives (MBO) and its role in developing employees’ technical and interpersonal skills of the startups companies in Lebanon. The studied sample was taken from Lebanon and distributed in three main cities (Beirut, Tripoli and Saida). This study summarized and showed the weaknesses of startups companies by adopting Management by Objectives (MBO). It also showed the development of the employees’ technical and interpersonal skills in companies that depend on the Management by Objectives (MBO) in their work without having in house continuous training programs. Add to that, it presented that Management by Objectives (MBO) motivates the employees to learn and develop independently, give them the freedom to make decisions and solve problems. Furthermore, it identified some of the challenges and problems faced by new graduates related to lack of technical and interpersonal skills when they graduate and collide in the market, especially, if there is absence of professional organizations that will help them to develop their skills and enable them to obtain greater and better opportunities in the future.